Peningkatan Kemampuan Berbicara Melalui Media Gambar Seri pada Anak Kelompok B TK Kuncup Harapan Soborejo Pringsurat Temanggung Semester I Tahun Pelajaran 2017/2018 - Andayani, Surip (CV. Supernova Office Stationary and Printing, 2022)
The Language is a very important communication tool in human life, because it serves as a tool to express thoughts and feelings to others. The problem faced by children in Group B of TK Kuncup Harapan Soborejo is that the children's speaking ability is still low. The purpose of this study was to determine the process of improvement and the magnitude of the increase in the speaking ability of the children of Group B Kindergarten Kuncup Harapan Soborejo Pringsurat in the first semester of the 2017/2018 academic year. The subjects of this study were 15 students in Group B of TK Kuncup Harapan Soborejo. The research was conducted in September 2017. Data collection methods used are observation, documentation and interviews. Based on the results of the research and discussion, it can be concluded that learning activities through serial picture media can improve the speaking ability of children in Group B Kindergarten Kuncup Harapan Soborejo Pringsurat Temanggung Semester I 2017/2018 Academic Year. This is evidenced by an increase in children's speaking ability at the time of pre-action by 13.3%, increasing to 33.3% in Cycle I, and reaching 86.7% in Cycle II. The success of learning improvement in improving children's speaking skills is indicated by the children being able to speak fluently, the children being able to ask and answering questions, and being able to speak in complete sentences (S-V-O/S-V-A).